Enzyme-immobilized Polymeric Capsules for Removal of Synthetic Phenol - Chiong, Tung (Curtin University, 2018)
Enzymatic phenol removal from wastewater is an important treatment approach to promote environmental sustainability. Whilst free peroxidases demonstrate efficient phenol degradation capabilities, they are disadvantaged by long-term stability and reusability. This research develops a novel system of plant-based peroxidase encapsulated in polymeric capsules for continuous phenol removal in a fluidized bed column. The process demonstrated scalability and commercial viability with 95% phenol removal efficiency.